2014
DOI: 10.2298/pac1401001t
|View full text |Cite
|
Sign up to set email alerts
|

Microwave sintering of biogenic hydroxyapatite ceramics for reconstructive surgery

Abstract: Ceramics based on biogenic hydroxyapatite have been produced via a microwave sintering at 1000?C for 5, 10, 15, 20 and 30 min. It was shown that all of the ceramics studied exhibit volumetric shrinkage (2.3- 4.6 %), which increases with increasing sintering time at maximum temperature. It was established that the total porosity did not depend on sintering time at 1000?C and was equal to 38-40 %. Moreover, in all of the materials an open porosity dominated. The ultimate compression strength wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Sintering is acute for HAp ceramic, shaping micro-structural properties. Tovstonoh, et.al [3] has researched on the sintering of bovine bone by calcination at 800 ºC for 3 h and sintering by microwave at 1000 ºC for 5 to 30 minutes. He has mentioned that the total porosity of biogenic hydroxyl apatite was not dependent on sintering time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sintering is acute for HAp ceramic, shaping micro-structural properties. Tovstonoh, et.al [3] has researched on the sintering of bovine bone by calcination at 800 ºC for 3 h and sintering by microwave at 1000 ºC for 5 to 30 minutes. He has mentioned that the total porosity of biogenic hydroxyl apatite was not dependent on sintering time.…”
Section: Introductionmentioning
confidence: 99%
“…Mangkonsu, et.al [4] have compared the usual furnace and microwave sintering of calcium phosphate at 1300 ºC and reached to 3.15 g/cm 3 density, but due to the α-TCP formation the expansion and cracks on the surface of their samples were reported. They also showed that both conventional and microwave sintered samples were biocompatible.…”
Section: Introductionmentioning
confidence: 99%